Extract and Powder of Epilobium Angustifolium in Bakery Products - Nevskaya E.; Zueva A.; Belyaev A. (Техника и технология пищевых производств)
Introduction. The modern food industry is currently facing the problem of the appropriate use of inexpensive and affordable domestic plant materials as an important source of vital substances. They can be used in formulations and production technologies of fortified functional foods. The present research featured the development and assessment of the quality of wheat bread fortified with willow weed (Epilobium Angustifolium). Study objects and methods. Samples of wheat bread were prepared from wheat baking flour of the highest grade. The extract and powder were prepared from crushed grass of Epilobium Angustifolium. The sensory and physico-chemical quality indicators of wheat bread samples were determined by conventional methods. The Harrington desirability function was used to improve the sensory properties of the wheat bread samples. Results and discussion. The interval ranges of values of the generalized desirability function were used to establish the values of this function for all samples of wheat bread fortified with Epilobium Angustifolium. The values proved to be in the range marked as «good»: D = 0.6927–0.6908. The powder of Epilobium Angustifolium increased the content of potassium in 100 g of bread by 5–12%, calcium – by 12–30%, magnesium – by 3–7%, and phosphorus – by 2–6%. When the extract was applied, the content of potassium and calcium increased by 7% and 13%, respectfully, while the content of magnesium and phosphorus increased by 4%. Conclusion. The extract of Epilobium Angustifolium fortified the samples of wheat bread with important mineral elements and increased their nutritional value. The physico-chemical indicators of the test samples did not deteriorate. The optimal dose of Epilobium Angustifolium powder was 3% vs. total flour mass. The sample of wheat bread with 3% of willow weed powder demonstrated good quality indicators, and its physico-chemical indicators met the requirements of the standard. The nutritional value of wheat bread samples fortified with Epilobium Angustifolium powder increased due to the larger content of phosphorus, magnesium, calcium, and potassium.